Environmental and Sustainability Management Accounting (EMA) for The Development of Sustainability Management and Accountability : Guest Editorial (Issues in Social and Environmental Accounting (ISEA), 2015)
This guest editorial provides an overview of the key themes and contributions presented in a special issue on Environmental and Sustainability Management Accounting (EMA). The authors highlight the role of EMA and Environmental Management Systems (EMS) in supporting organisations—both in developed and developing countries—to improve sustainability performance through measuring environmental impacts, increasing awareness, enhancing internal processes, and informing strategic decision-making. The editorial summarises five studies that collectively explore how internal and external organisational factors influence environmental practices, CSR performance, and financial outcomes. These studies employ a variety of theoretical frameworks—including sustainability balanced scorecards, strategy orientation models, and corporate governance perspectives—and use different methodologies across diverse national contexts. The editors conclude that EMA and EMS provide valuable tools for advancing sustainability management, and the insights from these papers contribute to expanding theoretical understanding and identifying future research opportunities in environmental and sustainability accounting.